2021
DOI: 10.3390/ani11113286
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Herbal Compounds Quercetin and Curcumin on Cellular and Molecular Functions of Bovine-Milk-Isolated Neutrophils toward Streptococcus agalactiae Infection

Abstract: Herbal phytochemicals featuring active ingredients including quercetin and curcumin have shown potential in treating human and animal diseases. The current study investigated their potential function in vitro for host immunomodulation associated with Streptococcus agalactiae subclinical bovine mastitis via milk-isolated neutrophils. Our results showed a positive influence on cellular migration, reactive oxygen species (ROS) generation, phagocytosis, and bacterial killing as well as neutrophil extracellular tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Alternatively, though, phagocytosis and related processes may just be downstream of the immune activation we observe in all high-intervention groups. Correspondingly, in the context of bovine mastitis, quercetin was shown to enhance phagocytosis and bacterial killing (Disbanchong et al, 2021) and it promotes the expression of genes involved in phagocytosis in bovine neutrophils (Srikok, Nambut, Wongsawan, & Shuammitri, 2017). Overall, the gene expression data align with the inflammation marker data, adding mitochondrial and immune aspects, and they suggest apoptosis and related processes triggered in the highest intervention group, possibly due to the senolysis of senescent blood cells.…”
Section: A Strawberry-based Intervention Improves Mitochondrial Immun...mentioning
confidence: 52%
“…Alternatively, though, phagocytosis and related processes may just be downstream of the immune activation we observe in all high-intervention groups. Correspondingly, in the context of bovine mastitis, quercetin was shown to enhance phagocytosis and bacterial killing (Disbanchong et al, 2021) and it promotes the expression of genes involved in phagocytosis in bovine neutrophils (Srikok, Nambut, Wongsawan, & Shuammitri, 2017). Overall, the gene expression data align with the inflammation marker data, adding mitochondrial and immune aspects, and they suggest apoptosis and related processes triggered in the highest intervention group, possibly due to the senolysis of senescent blood cells.…”
Section: A Strawberry-based Intervention Improves Mitochondrial Immun...mentioning
confidence: 52%
“…In addition, further research showed that CUR has good antibacterial effects, which may be closely related to the reduced aggregation of FtsZ raw wire and the interrupted cell division, thereby inhibiting the proliferation of bacteria. Moreover, CUR can also induce bacterial apoptosis to express a sterilization effect [ 59 , 60 ]. A previous study demonstrated that CUR could increase the apoptosis protein RECA expression in E. coli , leading to ROS accumulation, membrane exfoliating and calcium ions, and DNA fragments, and eventually induced the bacterial apoptosis [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pellets were rinsed twice with cold Hanks’ Balanced Salt Solution (HBSS) and resuspended in cold Roswell Park Memorial Institute 1640 (RPMI 1640) medium containing 1% heat-inactivated foetal bovine serum (FBS, Gibco, Thermo Fisher Scientific, Waltham, MA, USA). The Trypan blue exclusion method and cytospin were used to assess the viability and to determine the neutrophil purity, respectively [ 19 ]. The results show a viability rate of over 95%, while the purity of the cells was more than 85%.…”
Section: Methodsmentioning
confidence: 99%
“…As major causes of bovine mastitis, Staphylococcus aureus (SAU), Streptococcus agalactiae (SAG) [ 19 ], and Streptococcus uberis (SUB) [ 27 ] were selected for the current study. Bovine non-aureus staphylococci and mammaliicocci (NASM); Staphylococcus hominis (SHO) and Staphylococcus chromogenes (SCH); lactic acid bacteria (LAB); and two isolates of Weissella paramesenteroides (WPA1 and WPA2) with antimicrobial activity against S. aureus or Escherichia coli were used as minor pathogen-causing bovine mastitis in the entire experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation